C29. Intensive Care Unit-Acquired Weakness: Understanding Where We Are and Where We Should Go 2011
DOI: 10.1164/ajrccm-conference.2011.183.1_meetingabstracts.a4255
|View full text |Cite
|
Sign up to set email alerts
|

Selective Diaphragm Muscle Weakness Following Contractile Inactivity During Thoracic Surgery

Abstract: Postoperative pulmonary complications are significant contributors to morbidity in patients who have undergone upper abdominal, thoracic, or cardiac surgery. The pathophysiology of these complications might involve postoperative inspiratory muscle weakness. The nature of postoperative inspiratory muscle weakness is unknown. Objective To investigate the effect of surgery on the functioning of the diaphragm, the main muscle of inspiration. Methods Serial biopsies from the diaphragm and the latissimus dorsi muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…11 Methods of providing inspiratory muscle training include inspiratory threshold pressure loading, isocapnic/normocapnic hyperpnoea, and inspiratory resistive flow loading. 13 Respiratory muscle weakness has been suggested as a contributor in the development of postoperative pulmonary complications 14,15 and reductions in both inspiratory and expiratory muscle strength have been demonstrated up to 12 weeks postoperatively. 14,16 It is, therefore, conceivable that preoperative interventions to strengthen the inspiratory muscles may improve postoperative recovery and reduce the incidence of postoperative pulmonary complications.…”
Section: Introductionmentioning
confidence: 99%
“…11 Methods of providing inspiratory muscle training include inspiratory threshold pressure loading, isocapnic/normocapnic hyperpnoea, and inspiratory resistive flow loading. 13 Respiratory muscle weakness has been suggested as a contributor in the development of postoperative pulmonary complications 14,15 and reductions in both inspiratory and expiratory muscle strength have been demonstrated up to 12 weeks postoperatively. 14,16 It is, therefore, conceivable that preoperative interventions to strengthen the inspiratory muscles may improve postoperative recovery and reduce the incidence of postoperative pulmonary complications.…”
Section: Introductionmentioning
confidence: 99%
“…We, and others have shown that cardio-thoracic surgeries lasting 2 to 6 hours lead to gene expression changes compatible with the early stages of VIDD development (Huang et al, 2011; Welvaart et al, 2011a). …”
Section: Effects Of MV On Diaphragm Function: Human Studiesmentioning
confidence: 72%
“…To date, approximately 19 studies have examined the impact of MV on the structure and function of the human diaphragm, including dependent measures such as gene expression (Huang et al, 2011; Welvaart et al, 2011a), diaphragm thickness and pressure generation (Grosu et al, 2012; Hermans et al, 2010; Jaber et al, 2011b), muscle fiber CSA (Levine et al, 2008) or cellular and molecular mechanisms of VIDD (Hussain et al, 2010; Picard et al, 2012; Tang et al, 2011). The human studies have generally corroborated the animal study findings.…”
Section: Effects Of MV On Diaphragm Function: Human Studiesmentioning
confidence: 99%
“…Eligibility criteria for intraoperative hemidiaphragm stimulation included adults (18-80 years) scheduled for non-emergent clinical cardiothoracic surgeries anticipated to last at least 3 hours, enabling 4 or more bouts of phrenic stimulation. Patients were ineligible to participate for any of the following: (1) history of surgery to the diaphragm or pleura, (2) severe obstructive lung disease (FEV1 <40% predicted), (3) restrictive lung disease, (4) severe chronic heart failure (NYHA class IV), ( 5) chronic kidney disease with serum creatinine >1.6 mg/dL, (6) body mass index <20 or >40 kg/m2, (7) chronic uncontrolled metabolic disease, (8) concurrent neoplastic or myopathic illness, or (9) use of immunosuppressants, corticosteroids, or aminoglycoside antibiotics within 28 days of surgery. The protocol was approved by the University of Florida Institutional Review Board and prospectively registered (NCT03303040).…”
Section: Patientsmentioning
confidence: 99%
“…However, extended periods of MV can lead to ventilator-induced diaphragm dysfunction (VIDD), which increases chances of medical complications and has been recognized as a major clinical barrier to weaning among patients who require prolonged MV support (1). The signs of VIDD occur within hours of MV and include increased protein degradation and loss of force generation (2)(3)(4)(5)(6). The loss of force in VIDD occurs due to fiber atrophy and contractile dysfunction (4,7,8), with the latter being documented by a decrease in force divided per cross-sectional area (specific force).…”
Section: Introductionmentioning
confidence: 99%